A methodology to measure the effectiveness of academic recruitment and turnover. Issue 1 (February 2016) - Abramo, Giovanni; D'Angelo, Ciriaco Andrea; Rosati, Francesco
Highlights: The ability to attract the best professors is a key competence of top universities. Eight indicators to assess the effectiveness of recruitment and turnover are presented. Four indicators of effectiveness of overall mobility are presented. The methodology is applied to the Italian case but can be employed elsewhere. Abstract: We propose a method to measure the effectiveness of the recruitment and turnover of professors, in terms of their research performance. The method presented is applied to the case of Italian universities over the period 2008–2012. The work then analyses the correlation between the indicators of effectiveness used, and between the indicators and the universities' overall research performance. In countries that conduct regular national assessment exercises, the evaluation of effectiveness in recruitment and turnover could complement the overall research assessments. In particular, monitoring such parameters could assist in deterring favoritism, in countries exposed to such practices.